2022
DOI: 10.3390/ijerph192315792
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Implementation Outcome Scales for Digital Mental Health (iOSDMH): Experiences from Six Randomized Controlled Trials

Abstract: Objectives: Measuring implementation outcomes for digital mental health interventions is essential for examining the effective delivery of these interventions. The “Implementation Outcome Scale of Digital Mental Health” (iOSDMH) has been validated and used in several trials. This study aimed to compare the iOSDMH for participants in six randomized controlled trials (RCTs) involving web-based interventions and to discuss the implications of the iOSDMH for improving the interventions. Additionally, this study ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
2
5
1
Order By: Relevance
“…Regarding secondary outcomes, the present study found significant favorable effects on psychological distress and role-oriented future prospects, one of the subscales of well-being at work. These findings are in accordance with previous studies 13,34,36–38 . It is well-known that feeling pleasure or mastery in specific activities reduces psychological distress (ie, depression and anxiety) 16,17 and gaining mastery and self-efficacy enforces subjective well-being, such as setting and achieving goals 19–21 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding secondary outcomes, the present study found significant favorable effects on psychological distress and role-oriented future prospects, one of the subscales of well-being at work. These findings are in accordance with previous studies 13,34,36–38 . It is well-known that feeling pleasure or mastery in specific activities reduces psychological distress (ie, depression and anxiety) 16,17 and gaining mastery and self-efficacy enforces subjective well-being, such as setting and achieving goals 19–21 .…”
Section: Discussionsupporting
confidence: 91%
“…Regarding implementation outcomes, the proportion of positive responses (ie, answered “agree” or “relatively agree”) on each item were more than 60.0% on every subscale: acceptability, appropriateness, feasibility, and overall satisfaction. Compared with five programs in previous studies, 36 the length of this iBA program was highly implementable, and the rate of overall satisfaction was relatively high. Participants’ comments revealed that they might have gained self-efficacy through making action plans or reflecting on their own.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The iOSDMH for users has a total of 19 items, consisting of acceptability (3 items), appropriateness (4 items), feasibility (6 items), satisfaction (1 item), and harm (5 items). Internal consistency, structural validity, and known-class validity were confirmed in the scale development study and a previous systematic review [ 38 , 39 ]. We calculated the total scores of each subscale, and the overall score comprised acceptability, appropriateness, feasibility, and satisfaction.…”
Section: Methodssupporting
confidence: 60%
“…As potential modifiers for the effect, the operating system in personal smartphones (iOS [reference] and Android), age (20-30 years, 40-50 years [reference], and 60 years or older), gender (male [reference], female), and the total K6 score at baseline were entered into the model as covariates. Mean scores of implementation outcomes based on iOSDMH for users were compared with those reported in previous mHealth studies [ 39 ]. All analyses were conducted at the individual level using SPSS Statistics (version 25.0, IBM Corp).…”
Section: Methodsmentioning
confidence: 99%